Estimativa da demanda de água residencial urbana no estado do Ceará - Fontenele, Raimundo Eduardo Silveira (2011)
This study determined a function demand for residential water. The data were stratified by geographic areas according to the level of regularity of water supply to the households. Income, price, number of rooms and persons in the households were found to be the main variables influencing the level of water consumption. Differences between: i) households connected to the water and sewage systems and those connected only to the water system; ii) households with up to 20 m3 of water consumption and those with consumption between 20 and 50 m3 and finally those with consumption above 50 m3 were surveyed. The results of the residential water demand were, in general, statistically significant and the coefficients presented the expected sign. These results are important tools to help decide on the tariffs to be charged to the consumers and on the investments to be made in the sector.